Review and Prospect of Urban Waterlogging Decision Support System - LU Jiantao; HOU Guibing; LI Yuanyuan; CHEN Junxian; XUE Jiao (Renmin Zhujiang)
With advantages of reasonable, rapid and accurate aid decision making, the urban waterlogging decision support system can comprehensively improve the ability of flood and waterlogging control. This paper systematically reviews the research progress of urban waterlogging decision support system and its application in large and medium-sized cities, points out the problems of low data accuracy, narrow research scope and slow calculation speed in system development and application, forecasts the development trend of the system, and puts forward several solutions, such as strengthening the multi-source data collection of urban waterlogging, improving the integrated forecasting of waterlogging in river basin and urban, and optimizing the overall calculation speed of the model.